1984
DOI: 10.1016/s0735-1097(84)80089-3
|View full text |Cite
|
Sign up to set email alerts
|

Inferior ST segment depression during acute anterior myocardial infarction: Clinical and angiographic correlations

Abstract: This study was performed to determine whether inferior ST segment depression during early stages of acute transmural anterior myocardial infarction identifies patients with multivessel coronary artery disease and additional inferior ischemia. Coronary and left ventricular angiography were performed within 3.4 months in 33 patients with acute transmural anterior infarction. Initial electrocardiograms, 2 to 5 hours after onset of chest pain, revealed significant ST segment depression (greater than or equal to 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(18 citation statements)
references
References 26 publications
2
13
3
Order By: Relevance
“…ST-depression, seen as the reciprocal changes in the ECG tracings, is probably the effect of a larger ischemic area in remote myocardium during STEMI, regarding or according to total occlusion of the infarct-related artery, and affects mortality accordingly. Previous studies reported a correlation between the presence of reciprocal changes and multivessel disease, 4 and we have found also a correlation between poor STN and 3-vessel disease. Thus, worse longterm mortality in cases of poorer STN may be at least partly influenced by multivessel disease.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…ST-depression, seen as the reciprocal changes in the ECG tracings, is probably the effect of a larger ischemic area in remote myocardium during STEMI, regarding or according to total occlusion of the infarct-related artery, and affects mortality accordingly. Previous studies reported a correlation between the presence of reciprocal changes and multivessel disease, 4 and we have found also a correlation between poor STN and 3-vessel disease. Thus, worse longterm mortality in cases of poorer STN may be at least partly influenced by multivessel disease.…”
Section: Discussionsupporting
confidence: 83%
“…3 Furthermore, inferior ST-segment depression during an anterior infarction was shown to be associated with more extensive infarction, greater morbidity and higher frequency of multivessel coronary disease, which suggested that ST depression was not a reciprocal change, but rather ischemia in adjacent remote regions. 4 However, the significance of the dynamic changes in the reciprocal ST-segment depression after interventional treatment of patients with STEMI is unknown and became the aim of this study.…”
mentioning
confidence: 99%
“…However, in the present study, there was no difference in the frequency of patients with ST-segment depression in the inferior leads between patients with and without ST-segment depression in the lateral chest leads. Considering the results of the present study and previous studies with regard to STsegment depression in the inferior leads in anterior wall AMI, 4,6,8,12,13,19 there may be some differences in infarct size and prognosis between patients with ST-segment depression in the inferior leads and those with ST-segment depression in the lateral chest leads. Further investigation is Japanese Circulation Journal Vol.63, November 1999 needed to precisely clarify any differences in clinical features according to the site of ST-segment depression in anterior wall AMI.…”
Section: St-segment Depression In the Inferior Leads Versus In The Lasupporting
confidence: 60%
“…6,8,12,19 Therefore, the frequency of patients with ST-segment depression in the inferior leads could affect our results. However, in the present study, there was no difference in the frequency of patients with ST-segment depression in the inferior leads between patients with and without ST-segment depression in the lateral chest leads.…”
Section: St-segment Depression In the Inferior Leads Versus In The Lamentioning
confidence: 99%
See 1 more Smart Citation